The strategic use of metaphor in political discourse: Critical Metaphor Analysis - Tito Dimas Atmawijaya (Russian Journal of Linguistics)
Political discourse is increasingly shaped by crisis events that demand immediate rhetorical responses from leaders. While metaphors have been extensively studied in political communication, understanding their strategic deployment during crisis moments remains understudied. This gap is particularly significant given the potential impact of crisis-driven metaphorical framing on public perception and policy outcomes in democratic societies. This study aims to identify how metaphorical language is strategically deployed in political crisis communication and its role in shaping public perception and policy debates. The research focuses on Donald Trump’s 2024 nomination acceptance speech following an assassination attempt, offering a unique case study of crisis-response rhetoric in a high-stakes political context. The methodology combines Critical Metaphor Analysis with metaphor scenario identification, employing the Pragglejaz Group’s Metaphor Identification Procedure (MIP) modified for political discourse. The 12,287-word speech transcript was analyzed to identify and categorize metaphorical expressions and scenarios. Inter-coder reliability was ensured through Cohen’s kappa coefficient measurements and consensus meetings. The findings reveal sophisticated applications of interlinked metaphor scenarios that serve multiple rhetorical functions. Key scenarios identified include survival as divine intervention, immigration as invasion, and nation as construction project, creating coherent narrative arcs linking personal crisis to national renewal. The analysis demonstrates how these scenarios simplify complex issues, evoke emotional responses, and construct leadership narratives. This research contributes to crisis communication theory by demonstrating how metaphor scenarios are strategically deployed to shape public perception during pivotal political moments. The findings have important implications for media literacy education and the development of ethical guidelines for metaphor use in political communication, particularly during crisis events.